Relationships between organic carbon fractions and physical properties of an Argentine soil under three tillage systems - Cosentino, Diego; Costantini, Alejandro; Segat, Andrea; Fertig, Matías (Pesquisa Agropecuaria Brasileira, 1998)
A field trial was carried out on a Typic Argiudoll soil cropped to corn, located at Córdoba, Argentina. The effect of three tillage systems: direct drilling (DD), reduced tillage (RT) and conventional tillage (CT), on organic carbon (OC), microbial biomass carbon (MBC), structural stability, aggregates density and percentage of macroaggregates greater than 2 mm was studied. OC was significantly higher in DD plots. Also, DD was the only system that presented significant differences in depth. MBC showed a similar trend to OC, but the decrease of its contents in RT and CT were greater than DD. The highest soil structural stability was obtained in DD and the lowest in CT. The decrease in structural stability (in percentage) was greater than the decrease in OC and MBC. Aggregates density did not show differences between tillage systems for the surface samples. All the tillage systems presented the highest values of aggregates density at 5-15 cm. A greater percentage of macroaggregates was found in DD for both sampling depths. When MBC content was considered throughout the sampling depth, a high correlation with macroaggregates percentage was found.